A link between noise parameters and light exposure in GaAs pHEMT's. (March 2015) - Caddemi, Alina; Crupi, Giovanni; Salvo, Giuseppe
Highlights: DC and microwave characterization of an advanced GaAs pHEMT. Investigation of transistor performance under optical illumination. Scattering and noise parameter measurements. Abstract: This work presents an experimental investigation and relevant discussion of the link existing between noise parameters and light exposure of GaAs pseudomorphic HEMT's at microwave frequencies. A 100 μm gate width AlGaAs/InGaAs/GaAs heterostructure device has been illuminated with CW visible laser light (650 nm) and a systematic analysis has been performed by examining the device behavior under controlled bias current conditions. Significant effects have been brought to evidence in the 2–26 GHz noise parameters F min, Γ opt and R n measured in the different conditions. A clear correlation has been found between the level of degradation of the noise parameter behavior and the light exposure.